Trapping endoplasmic reticulum with amphiphilic AIE-active sensor via specific interaction of ATP-sensitive potassium (KATP) - Zhu, Zhirong; Wang, Qi; Liao, Hongze; Liu, Ming; Liu, Zhenxing; Zhang, Youheng; Zhu, Wei-Hong (National science review, 2021)
Abstract The current aggregation-induced emission luminogens (AIEgens) sometimes suffer from poor targeting selectivity due to undesirable aggregation in the hydrophilic biosystem with ‘always-on’ fluorescence or unspecific aggregation in the lipophilic organelle with prematurely activated fluorescence. Herein, we report an unprecedented ‘amphiphilic AIEgen’ sensor QM-SO3-ER based on the AIE building block of quinoline-malononitrile (QM). The introduced hydrophilic sulfonate group can well control the specific solubility in a hydrophilic system with desirable initial ‘fluorescence-off’ state. Moreover, the incorporated p-toluenesulfonamide group plays two roles: enhancing the lipophilic dispersity, and behaving as binding receptor to the adenosine triphosphate (ATP)-sensitive potassium (KATP) on the endoplasmic reticulum (ER) membrane to generate the docking assay confinement effect with targetable AIE signal. The amphiphilic AIEgen has for the first time settled down the predicament of unexpected ‘always-on’ fluorescence in the aqueous system and the untargetable aggregation signal in the lipophilic organelle before binding to ER, thus successfully overcoming the bottleneck of AIEgens' targetability. An unprecedented ‘amphiphilic AIEgen’ sensor QM-SO3-ER well settlesdown the predicamentof unexpected ‘always-on’ fluorescence in aqueous system and untargetable aggregation signalin lipophilic organelle, thus overcoming the bottleneck of AIEgen targetability.